Optimization of Dynamix Cement Inventory Planning with Tsukamoto's Fuzzy Inventory Method at PT TRACK - Gusti Nurina Azhariani; Tedjo Sukmono (Universitas Muhammadiyah Sidoarjo, 2022)
In 2021, PT TRACK has an average Dynamix Cement inventory of 1,488 sacks/month and the highest inventory can reach 2,240 sacks. The high inventory capacity has an impact on inventory capacity that exceeds the maximum inventory limit (overload). This study aims to determine the optimal amount of Dynamix Cement inventory at PT TRACK so that it does not cause inventory overload. The method used is Fuzzy Inventory Control Tsukamoto. Several stages carried out in this research include (a) forming Fuzzy sets, (b) forming rules (c) inference, and (d) affirmation (defuzzification). The results of this study showed that the optimal supply of Semen Dynamix at PT TRACK in the period December 2020 to December 2021 was 1350 sacks, 1480 sacks, 1300 sacks, 1290 sacks, 1300 sacks, 1350 sacks, 1370 sacks, 1490 sacks, 1790 sacks, 1510 sacks, 1280 sacks, 1300 sacks, and 1320 sacks. Based on the estimated inventory of PT TRACK's Dynamix Cement, the total inventory of Dynamix Cement in the next period using the Tsukamoto Fuzzy Inventory method is 1380 sacks.